Blind separation of fluorescence spectra using sparse non-negative matrix factorization on right hand factor - Yang, Ruifang; Zhao, Nanjing; Xiao, Xue; Yu, Shaohui; Liu, Jianguo; Liu, Wenqing (Journal of chemometrics, 2015)
Sparse non‐negative matrix factorization on right side factor (SNMF/R) has better performance in feature extraction than non‐negative matrix factorization. In this work, SNMF/R was first used to separate the overlapped three‐dimensional fluorescence spectra of polycyclic aromatic hydrocarbons mixtures in pure water, lake water, and river water, respectively. It is found that the similarity coefficients between the acquired three‐dimensional spectra and the corresponding reference spectra with random initials are all above 0.80; the recognition rate of SNMF/R is higher than that of PARAFAC and non‐negative matrix factorization algorithms, especially in the case of lake water and river water samples. In addition, SNMF/R does not need any initialization scheme designing during spectra separation. These results demonstrate that SNMF/R is an appropriate algorithm to separate the overlapped fluorescence spectra of polycyclic aromatic hydrocarbons in aquatic environment accurately and effectively. Copyright © 2015 John Wiley & Sons, Ltd. Sparse non‐negative matrix factorization on right side factor (SNMF/R) was used to separate the overlapped three‐dimensional fluorescence spectra of polycyclic aromatic hydrocarbons mixtures in pure water, lake water, and river water, respectively. Results illustrate that SNMF/R can extract source spectra more accurately with similarity coefficients between the recognized three‐dimensional spectra and the reference spectra of all above 0.80 and recognition rate higher than that of PARAFAC and NMF algorithms.